THE INFLUENCE OF WEBSITE-BASED SUSTAINABILITY REPORTING AND CAPITAL STRUCTURE ON FIRM VALUE (Study of IDX ESG Leaders) - Sesylia Mohune; Muliyani Mahmud; Mentari Rizki Sawitri Pilomonu (PT. Jurnal Center Indonesia Publisher, 2026)
The phenomenon of increasing attention toward environmental and sustainability issues has driven companies to improve information transparency, moving beyond mere financial reports to include non-financial disclosures. One form of this transparency is realized through website-based sustainability reporting, which allows companies to convey sustainability information more openly and accessibly to stakeholders. On the other hand, capital structure decisions remain a fundamental factor that can potentially influence market perceptions of firm value, as they relate to the balance between internal and external funding in supporting operational continuity and growth strategies. This study aims to determine the influence of website-based sustainability reporting and capital structure on firm value through multiple linear regression analysis. Using a quantitative approach and secondary data obtained from annual reports and official company websites, the study focuses on issuers consistently listed in the IDX ESG Leaders index during the 2023–2024 period. The sample selection utilized purposive sampling, resulting in 20 companies with a total of 40 data observations. Firm value was measured using the Tobin’s Q ratio, the level of sustainability reporting disclosure was proxied through the Sustainability Report Disclosure Index (SRDI) based on GRI 2021 standards, and capital structure was measured by the Debt to Equity Ratio (DER). The partial results of the study show that website-based sustainability reporting has a positive coefficient but no significant effect on firm value. Similarly, capital structure shows a positive direction but is not statistically significant. Furthermore, the two variables simultaneously have no significant effect on the firm value of IDX ESG Leaders issuers. These findings indicate that although website-based sustainability disclosure and capital structure tend to have a direct relationship with firm value, the influence is not yet strong enough to significantly affect market valuation within a group of issuers that already meet sustainability criteria. Consequently, the firm value of IDX ESG Leaders issuers is not solely determined by the level of website-based sustainability disclosure or the company's capital structure.